Vertrek Dr. Beel naar Indonesië. V.l.nr. zittend: Sassen, v. Schaik, Beel, Drees, daarachter Götzen en Schokking
Vertrek Dr. Beel naar Indonesië. V.l.nr. zittend: Sassen, v. Schaik, Beel, Drees, daarachter Götzen en Schokking.